Strategies to Combat Antimicrobial Resistance from Farm to Table. Issue 1 (2nd January 2023) - Freeland, Gabriella; Hettiarachchy, Navam; Atungulu, Griffiths G.; Apple, Jason; Mukherjee, Soma
ABSTRACT: Antimicrobial resistance is a growing problem globally due to the overuse of antimicrobials in agriculture, food processing, food safety, and medical fields and becoming an increasing concern of resistant microbes. This review briefly explores the use of antimicrobial, the emergence of – antimicrobial resistance, and the spreading of resistance vertically and horizontally. The focus of this article is on human practices from farm to table contributing to the growing concern of antimicrobial resistance (AMR). It also discusses various monitoring programs currently in place, and the economic burden and mortality caused by antimicrobial resistance. Finally, the review proposes possible approaches to overcome the problem, such as reducing the use of antimicrobial and developing natural methods of handing food safety initiative and treating resistant pathogens (e.g. probiotics). The main findings showed that use of antibiotics in various field from crop cultivation to processing and preservation inducing the resistance to these bacteria in the USA and developing countries. Induced resistant genes are gradually spreading in a multidirectional way to the microbiome. This can only be mitigated by restrictive measures and litigation on the unnecessary use of antibiotics. Also, the use of organic/bio-control agents to prevent microbes should be encouraged and popularized.